2021
DOI: 10.1109/jstars.2021.3058421
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mapping of Long-Term Forest Disturbance and Recovery Dynamics in the Subtropical China Using All Available Landsat Time-Series Imagery on Google Earth Engine Platform

Abstract: to 2019. The annual variation patterns of forest gain and loss area were associated with the changes in forestry policies and large disturbance events. Our assessments on the long-term and fine scale forest dynamic patterns will help evaluate the effectiveness of forest management practices and forestry polices on forest resource sustainability, and climate change and greenhouse gases mitigation in Jiangxi Province and China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…They argued that this combined method is more accurate in detecting forest gain/loss due to large-scale disturbance events. Based on our previous study [46], we also found that this combination method can be effectively applied to detect the impacts of disturbance. In the future, we will apply this combined method to estimate forest damage in response to other devastating typhoon events in China.…”
Section: Uncertainties Implications and Outlooksmentioning
confidence: 85%
“…They argued that this combined method is more accurate in detecting forest gain/loss due to large-scale disturbance events. Based on our previous study [46], we also found that this combination method can be effectively applied to detect the impacts of disturbance. In the future, we will apply this combined method to estimate forest damage in response to other devastating typhoon events in China.…”
Section: Uncertainties Implications and Outlooksmentioning
confidence: 85%
“…Based on multiple data comparisons, several previous studies have also indicated that the GFC product significantly underestimated the forest loss and gain area at stand [44], national [19,45], and global scales [46]. In addition, this product only covered recent years and missed the 1980-2000 period when China has experienced stronger disturbance and initializations of several afforestation projects [16]. Therefore, it is necessary to localize and improve the forest change detection methods for China by considering the complicated forest and topographic conditions and training and evaluating the algorithms using more intensive local observational data, and generate provincial and national forest loss and gain dataset using the validated methods.…”
Section: Introductionmentioning
confidence: 99%
“…Diseases outbreaks have affected 22,954 km 2 of forest area in 2019, and insects and pests have affected 81,146 km 2 of forest area according to the NFI report. In addition to forestry policies and disturbances, other factors such as elevation, local economic development condition, and local forestry policies were reported to affect forest gain and loss [16][17][18]. All above factors could greatly affect the spatial and temporal patterns in forest gain and loss at different scales; however, few regional studies have assessed their impacts in China [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and spectral resolutions offered by Landsat and MODIS are well-suited for deforestation analysis; hence, there are various studies dealing with deforestation that analyze datasets coming from Landsat and MODIS satellites ( [7], [14], [19]). With remote sensing, deforestation monitoring systems use a number of automatic methods based on change detection techniques [13], e.g., image processing and analysis methods [16], [30] or ML techniques [12], [35].…”
mentioning
confidence: 99%